Prognosis Analysis and Clinical Features of Orbital Cavernous Venous Malformations With Refractory Insidious Onset - Yang, Peng; Li, Yong; Liu, Hao-Cheng; Qiu, E.; Zhang, Jia-Liang; Ren, Jian; Jiang, Li-Bin; Liu, Hong-Gang; Kang, Jun (Frontiers in Oncology, 2022)
Objective: The present study aims to analyse the clinical presentation, treatment and prognosis of a group of patients with orbital cavernous venous malformation (OCVM) with an insidious onset. Method: The clinical data of 35 patients with OCVM treated at our centre between 2003 and 2020 were retrospectively analysed. The OCVMs were classified as one of six types (I–VI) according to the orbital position of the tumour. The clinical characteristics, treatment methods and follow-up results were recorded. Results: A total of 35 patients with OCVM under the optic nerve sheath in the orbital apex area or the common tendon ring (Types I and II) were included in the present study. In 20 cases (57.1%), patients were misdiagnosed with optic neuritis, and in 20 cases (57.1%), the tumour was not identified based on imaging. The presentation was acute or subacute in 23 cases (65.7%). All patients underwent surgery: transnasal surgery in 22 cases (62.9%) and craniotomy in 13 cases (37.1%). A total of 9 patients (25.7%) experienced postoperative complications, and 17 patients (48.6%) experienced vision improvement. The average patient age at first diagnosis was 43.3 ± 10.3 years, and the median follow-up period was 64.5 months. Overall, 14 patients (40%) experienced postoperative complications: postoperative blindness in 6 cases, postoperative vision loss in 8 cases and orbital apex syndrome in 7 cases. Conclusion: Patients with Type I and Type II OCVMs are the most complex cases. They have an insidious onset and are associated with a high rate of misdiagnosis and missed diagnosis. Acute and subacute decreases in visual acuity are mainly caused by OCVM haemorrhage. The difficulty of surgical treatment and the poor prognosis of postoperative vision are characteristics of this tumour. Transnasal surgery and craniotomy can be used to remove OCVMs located in the common tendon ring or optic canal as well as those involving the intracranial area through the supraorbital fissure. Meanwhile, the orbital approach (orbitotomy) has proven to be an effective method of treating OCVMs not involving the deep orbital apex and intracranial area.